PENGEMBANGAN E-LKPD BERBASIS CLIS MENGGUNAKAN LIVEWORKSHEET PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Kamila Kamila; Yeni Erita (Penerbit Lafadz Jaya, 2023)
This research is motivated by the lack of innovation in learning media, especially LKPD where this has an impact on the active role of students in learning. This is also because most of the media used in learning is still in the form of media images. So that media is needed that is in accordance with technological developments and is able to arouse the active role of students in learning. This study aims to develop CLIS-based E-LKPD using liveworksheets in integrated thematic learning in grade IV SD that are valid, practical and effective. The type of research used is Research and Development with the ADDIE development model. Data collection uses validation sheets, teacher and student response questionnaires as well as the results of student learning evaluations as a reference for testing effectiveness. The results of the validity test were 92.8% material validation, 91.6% media validation and 95% linguistic validation. Practicality test with a total teacher response of 96.1%. The response results of class IV students were 99.27%. And the results of the effectiveness test with the acquisition of N-Gain of 80.25%.